Creating a dialogic space for prospective teacher critical reflection and transformative learning. Issue 6 (2nd November 2017) - Liu, Katrina
Abstract: This research highlights the pedagogical significance of dialogic spaces in supporting critical reflection and transformative learning among prospective teachers in the United States. It finds that, with elucidation of the multiple voices and texts from prospective teachers' field experience, teacher educators can stimulate deep reflection to springboard transformative learning. It also finds that ePortfolios have strong potential to support a dialogic approach to reflection. However, it is also clear that, absent systematic observation and careful follow-up dialogue, the potential to move from reflection to transformative learning is limited. The findings will help teacher educators rethink the design and practice of supervision with ePortfolios, reinforcing that critical dialogue between the supervisor and the prospective teachers is key to supporting prospective teachers' critical reflection and transformative learning, and to improving their teaching practice.